THE INFLUENCE OF LEADERSHIP STYLE AND COMPENSATION ON TURNOVER INTENTION MEDIATED BY WORK MOTIVATION - Alfeus Hermanto; Melitina Tecoalu; Lidia Sandra (CV. Radja Publika, 2023)
This study aims to determine how much influence leadership and compensation styles have on turnover intention through work motivation at PT Ocommerce Capital Indonesia. The number of respondents in this study were 73 respondents. The data used is a type of quantitative data obtained from filling out questionnaires by all respondents using the census method. The analytical method used in this research is through the Structural Equation Model (SEM) approach using the SmartPLS program. The results of this study indicate that there is a significant influence of leadership style and compensation on work motivation as an intervening variable.